TINJAUAN YURIDIS PRAKTEK TRANSAKSI DERIVATIF PADA PERDAGANGAN VALUTA ASING - , Inayah,SH. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is intended to analiyze the practice of derivative transaction of foreign currency trade whether it has been conform to the contract law based on Civil Code of Indonesia and the law protection from onto parties of derivative transaction on foreign currency trade. The research type is normative, with complimentary of secondary data as the main material of the research analyze. Data analyze is done through normative and qualitative method, which is pretended to draw the problem that occurred in the practice whether it has been done in accordance with the ruling law. The result and analyze of data show that the practice of derivative of transaction has been done accordance with the rules of Civil Code. Due to this reason, the parties of the transaction may obtain legal protection based on article 1338, and article 1365 of Civil Code with the other ruling law.